Cannabis cultivation and depleted forest areas in the province of Taounate (Rif Southern, Morocco): landscape and economic repercussions - E. López Lara; H. Daïde; H. Chaouki (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.